2014 IEEE Symposium on Security and Privacy 2014
DOI: 10.1109/sp.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

SoK: Automated Software Diversity

Abstract: Abstract-The idea of automatic software diversity is at least two decades old. The deficiencies of currently deployed defenses and the transition to online software distribution (the "App store" model) for traditional and mobile computers has revived the interest in automatic software diversity. Consequently, the literature on diversity grew by more than two dozen papers since 2008.Diversity offers several unique properties. Unlike other defenses, it introduces uncertainty in the target. Precise knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
166
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 261 publications
(167 citation statements)
references
References 48 publications
0
166
0
Order By: Relevance
“…Forrest subsequently demonstrated stack-layout randomization as a defense against stack smashing [15]. Subsequent work on artificial diversity is extensive; Larsen et al [27] provide an overview.…”
Section: A Software Diversitymentioning
confidence: 99%
“…Forrest subsequently demonstrated stack-layout randomization as a defense against stack smashing [15]. Subsequent work on artificial diversity is extensive; Larsen et al [27] provide an overview.…”
Section: A Software Diversitymentioning
confidence: 99%
“…Initially, the problem seemed to be the coarsegrained nature of ASLR. This motivated many finer-grained code randomization schemes (systematized by Larsen et al [22]). However, Snow et al [35] demonstrated just-in-time code reuse (JIT-ROP) that exploits memory disclosure and malicious scripting to read the randomized code layout and construct a compatible code-reuse payload on the fly.…”
Section: Motivationmentioning
confidence: 99%
“…Prominent examples of these security enhancing mechanisms are control-flow integrity [1], code-pointer integrity [21], and fine-grained code randomization [22]. While these defenses raise the bar to exploitation relative to current countermeasures, they differ with respect to performance, practicality, and security.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the years since these seminal papers, many have explored the idea further. A recent survey of the area was presented in [32]. Address Space Layout Randomization (ASLR) is one of the most widely used applications of this technique.…”
Section: Introductionmentioning
confidence: 99%